Investigation of the association between clinical outcome and the cag pathogenicity-island and other virulence genes of Helicobacter pylori isolates from patients with dyspepsia in Eastern Turkey - Ozbey, Gokben; Demirel, Ulvi; Aygun, Cem; Ertas, Hasan Basri (Springer, 2013)
The aims of our work were to determine the presence of the cag pathogenicity-island (cag PAI) and other virulence genes of Helicobacter pylori recovered from patients with gastritis and peptic ulcer, and to investigate the correlation of these virulence genes with clinical outcome. The presence of the cagA, the promoter regions of cagA, cagE, cagT, and the left end of cag-PAI (LEC), cag right junction (cagRJ), the plasticity region open reading frames (ORFs), vacA and oipA genes among 69 H. pylori isolates were determined by polymerase chain reaction. Intact cag PAI was detected in only one (1.4%) isolate. The cagA gene was identified in 52.1% and 76.2% of isolates from patients with dyspepsia (gastritis and peptic ulcer), respectively. The plasticity region ORFs i.e. JHP912 and JHP931 were predominantly detected in isolates from peptic ulcer. Less than 25% of the isolates carried other ORFs. Types I, II and III were the most commonly found among the isolates. None of the isolates possessed type Ib, 1c, IIIb, IV and V motifs. The most commonly vacA genotypes were s1am1a and s1m2 in isolates with peptic ulcer and gastritis, respectively. The results confirmed that the prevalence of oipA (Hp0638) gene was 75% and 85.7% in patients with gastritis and peptic ulcer, respectively. Furthermore, vacA s1am1a positivity was significantly related to peptic ulcer (p < 0.05).
Keywords: Helicobacter pylori; gastritis; peptic ulcer; cag pathogenicity-island; polymerase chain reaction